Taking your iPod touch to the max - Sadun, Erica; SpringerLink (Online service) (Berkeley, CA : Apress, Inc., 2008)
An introduction to each of the iPod's onboard applications: connecting to the internet, sending and receiving e-mail, listening to music, watching videos, and synchronizing calendars. In addition there are hints, tips and suggestions to make the most of the iPod's hidden potential.
Includes index.
Keywords: iTunes; iPod (Digital music player); iPod (Digital music player) -- Handbooks, manuals, etc; Digital music players; Music -- Data processing -- Handbooks, manuals, etc; MP3 players -- Handbooks, manuals, etc; Pocket computers -- Handbooks, manuals, etc; Portable media players